The Macroeconomic Determinants of External Debt in Ottoman Empire: A Study of Data from 1881–1913 - Lotfi Demikha; Amir Shaharuddin; Mahmoud Mohamed Ali Mahmoud Edris (USIM Press, 2024)
JMIFR Vol.18 No.1 (June) 2021